2011
DOI: 10.1080/13811118.2011.566052
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Utilization in Major Depression

Abstract: Suicide attempters with major depression are at risk for repeat attempts and often do not utilize treatment. Identifying predictors of treatment non-utilization could inform interventions to motivate treatment use and reduce suicide risk in major depression. Two hundred and seventy three participants with a major depressive episode as part of a major depressive disorder or bipolar disorder, were assessed for socio-demographic and clinical characteristics at baseline and again 1 year later to identify predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…crowding index to be correlated with mental health services utilization and these items could be used in planning mental health promotion programs in Iran. Socioeconomic factors have already been reported as one of major correlates of MHS use in literature (20, 31, 41-44). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…crowding index to be correlated with mental health services utilization and these items could be used in planning mental health promotion programs in Iran. Socioeconomic factors have already been reported as one of major correlates of MHS use in literature (20, 31, 41-44). …”
Section: Discussionmentioning
confidence: 99%
“…Rate of MHS use have reported in wide range between 6.5% (in elderly) and 34.5% (in college students) during last year (20, 24-25). Subjects with mental illnesses (26-27), living in stressful conditions such as immigrants (28-29)and victims of crimes such as rape or violence reported higher rates (between 52%-72.5% in victims of rape (30-31), 37% in victims of intimate partner violence (32-33). Need for MHS in our study were similar to study in California in 2005 (34).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we observed that psychiatric hospitalizations and suicidal ideation were also associated to suboptimal adherence, suggesting that more severe patients are also less adherents. Alonzo et al (2011) warned about the poor utilization of treatment by suicide attempters with MD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the covariates used in the other regression models, time-updated measures of antidepressant medication use and psychotherapy visits were included – both as a proxy for depression severity as previous research has linked treatment utilization with depression severity. (41)…”
Section: Methodsmentioning
confidence: 99%